Entrance to St. James Barracks, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of a tree lined St. James Avenue, which leads to St. James Barracks which today is the training center for the Trinidad and Tobago Police Service.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Suburbs--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. James; Barracks--Trinidad and Tobago